PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM TRAFO PRODUCTION - Adeline Oktalia; Emilya; Joicelyn Agriffina; Monica Ella; Fitriana Aidnilla Sinambela (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study discusses how to manage demand and production capacity at UMKM Trafo Production. At the beginning of the pandemic, Trafo Production caused a fairly large negative impact on the world economy which had experienced a decline. Hence, this study aims to determine the types of demand patterns used by consumers, understand how to handle production capacity to meet consumer demand and to understand how to inventory demand with a waiting and queuing system. In this study, we use a qualitative descriptive analysis method, namely by describing or describing the UMKM Trafo Production in order to find out what services are provided by MSME and also the responses by consumers so that they can know the services provided and input from consumers through the interview method. In the results of the economic recovery that occurred when the implementation of the new normal era so that the number of service requests began to return to indicate a demand so that it experienced an increase by Trafo Production which required services in the field of videography, photos, logos and others related to postings on social media. The pattern of market demand for UMKM Trafo Production is also influenced by time, such as at the beginning of the month.